Aurangzeb the life and legacy of India's most controversial king - Truschke, Audrey (Stanford University Press, 2017)
The Mughal emperor Aurangzeb Alamgir is one of the most hated men in Indian history. Widely reviled as a religious fanatic who sought to violently oppress Hindus, he is even blamed by some for setting into motion conflicts that would result in the creation of a separate Muslim state in South Asia. This book invites students of South Asian history and religion into the world of the Mughal Empire, framing the contemporary debate on Aurangzeb's impact and legacy in accessible and engaging terms.